2018
DOI: 10.4236/ojce.2018.84029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Powder (Fe<sub>2</sub>O<sub>3</sub>) on Strength, Workability, and Porosity of the Binary Blended Concrete

Abstract: In this study, the effect of iron powder (Fe 2 O 3 ) on the compressive strength, tensile strength, workability, and porosity of the binary blended concrete were experimentally investigated. For this purpose, Portland cement was partially replaced by 1.5%, 2.5%, 3.5%, and 5% by weighing of iron powder. The amount of water-binder-ratio was considered constant. The workability of the fresh composite concrete was determined using cone Abrams method; mechanical properties were determined included compressive and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It offers a handy framework that enables an analyst to pick a suitable technique that might be applied to test the strength of cements. Largeau et al [23] studied how iron powder (Fe 2 O 3 ) affected the strength, workability, and porosity of binary blended concrete. The cone Abrams method was used to assess the new composite concrete's workability.…”
Section: Introductionmentioning
confidence: 99%
“…It offers a handy framework that enables an analyst to pick a suitable technique that might be applied to test the strength of cements. Largeau et al [23] studied how iron powder (Fe 2 O 3 ) affected the strength, workability, and porosity of binary blended concrete. The cone Abrams method was used to assess the new composite concrete's workability.…”
Section: Introductionmentioning
confidence: 99%
“…Iron dust used for the study is the waste produced from the iron ore-based industries [3]. This iron waste is usually used for landfills for its disposal and has been very environmentally dangerous as the heavy metals from this iron ore waste gets into the earth and subsequently into the underground water polluting it [4][5]. So, researchers found the novel use of this waste as a replacing material for the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…A notable positive effect of both red and black iron oxide particles on slump and compressive strength (up to 22–30%) was reported. Recently, Largeau et al [ 25 ] investigated the effect of Fe 2 O 3 on the strength and workability of a Portland cement concrete. They found that fine Fe 2 O 3 particles, ca.…”
Section: Introductionmentioning
confidence: 99%